2021
DOI: 10.1186/s13012-021-01111-5
|View full text |Cite
|
Sign up to set email alerts
|

Rapid versus traditional qualitative analysis using the Consolidated Framework for Implementation Research (CFIR)

Abstract: Background Qualitative approaches, alone or in mixed methods, are prominent within implementation science. However, traditional qualitative approaches are resource intensive, which has led to the development of rapid qualitative approaches. Published rapid approaches are often inductive in nature and rely on transcripts of interviews. We describe a deductive rapid analysis approach using the Consolidated Framework for Implementation Research (CFIR) that uses notes and audio recordings. This pap… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
153
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 275 publications
(153 citation statements)
references
References 36 publications
0
153
0
Order By: Relevance
“…Nevertheless, rapid approaches to qualitative analysis are gaining recognition as an acceptable methodology within limited timeframes and have been successfully applied to other contexts [ 10 ]. Comparative studies have demonstrated that rapid analysis techniques can generate similar findings to in-depth approaches [ 8 , 9 , 11 ]. In particular, they can allow researchers to work productively with partners, such as audit programmes, that often seek timely and actionable recommendations.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Nevertheless, rapid approaches to qualitative analysis are gaining recognition as an acceptable methodology within limited timeframes and have been successfully applied to other contexts [ 10 ]. Comparative studies have demonstrated that rapid analysis techniques can generate similar findings to in-depth approaches [ 8 , 9 , 11 ]. In particular, they can allow researchers to work productively with partners, such as audit programmes, that often seek timely and actionable recommendations.…”
Section: Discussionmentioning
confidence: 99%
“…We used a rapid approach to analysis and interpretation. Rapid techniques within qualitative analysis are considered appropriate to provide valid findings and recommendations within a short timeframe [ 8 11 ]. Our report follows the COREQ recommendations for qualitative studies [ 12 ] (Additional file 1 ).…”
Section: Methodsmentioning
confidence: 99%
“…Data collected during patient interview 2 as well as the clinician and nurse interviews will be analyzed using a rapid deductive analysis approach guided by the Theoretical Framework of Acceptability (TFA) [ 53 , 56 , 57 ]. We will develop a structured summary template for recording information focusing on acceptability, as defined by the TFA component constructs (affective attitude, burden, perceived effectiveness, ethicality, intervention coherence, opportunity costs, and self-efficacy), barriers to use, and opportunities for enhancement.…”
Section: Methodsmentioning
confidence: 99%
“…The CFIR provides the organizing framework for qualitative deductive coding and analysis of the clinician interviews. CFIR interviews will be administered and coded using a variation of the Rapid Analysis (RA) method, an alternative to in-depth analysis of interview data to allow for faster analysis and dissemination of implementation findings while using fewer resources [ 58 , 59 ]. In combination with the fidelity results, we will seek patterns of implementation facilitators and barriers, coded deductively to the CFIR domains and factors, as well as direction and strength of the association (valence) between factors and implementation success.…”
Section: Methodsmentioning
confidence: 99%